P428 Early and Late Fecal Calprotectin Remission - Analysis of a proactive Therapeutic Drug Monitoring Treatment Protocol. (27th May 2021) - Pedro, J; Rodrigues, I; Damião, F; Fernandes, S; Gonçalves, A R; Bernardo, S; Baldaia, C; Valente, A; Moura Santos, P; Correia, L; Tato Marinho, R
Abstract: Background: Fecal calprotectin (Fc) is an adequate surrogate marker for endoscopic activity in inflammatory bowel disease. The timing of Fc remission may have prognostic implications in patients under biologic therapy. Methods: Using a prospectively maintained database we followed 135 patients under a proactive therapeutic drug monitoring (pTDM) protocol aiming at an Infliximab trough level (IFXTL) between 5-10 µg/mL with sequential measurements of Fc. We evaluated the rates of early (at week 14) and late (after week 14) Fc remission (<250 µg/g) and associated clinical outcomes at 2-years of follow up. Results: 77 patients (57.0%) reached early Fc remission and 30 patients (22.2%) reached late Fc remission. Patients with late Fc remission presented higher Fc at baseline (1708.5 μg/g [681-3483] vs 803 μg/g [339-1477], P =0.006) and lower IFXTL at week 14 (2.71 µg/mL [1.24-6.30] vs 6.59 µg/mL [3.41-10.63], P =0.001) than patients with early Fc remission. However, by the end of follow-up, IFXTL were similar in both groups: 7.94 µg/mL (4.79-11.25) vs 8.54 µg/mL (6.49-11.07), P =0.514. In patients without early Fc remission, week 14 IFXTL did not differ between those with and without late Fc remission (2.71 µg/mL [1.24-6.30] vs 3.47 µg/mL [0.945-6.94], P =0.957), but significantly increased in late responders by the end of follow-up: 8.54 µg/mL (6.49-11.07) vs 4.37 µg/mL (1.77-7.49), P =0.002. Patients with early and late Fc remission presented similar rates of clinical remission (88.3% vs 83.0%, P =0.493), steroid-free clinical remission (79.1% vs 92.9% P =0.239), lower rates of IFX discontinuation (14.3% vs 16.7%, P =0.756), hospitalization (11.7% vs 13.3%, P= 0.815), and surgery (1.3% vs 3.3%, P =0.485). Conclusion: The magnitude of Fc at baseline and IFXTL at week 14 significantly influence the timing of Fc remission. The use of PTDM results in similar pharmacokinetics and clinical outcomes in both groups.